Factores de riesgo en la preeclampsia severa y su relación con el parto prematuro en el Hospital Alfredo Noboa Montenegro, agosto-noviembre 2022 - Carvajal Bermeo, Evelyn Yessenia (2023)
ABSTRACT The present research study entitled "Risk factors in severe preeclampsia and its relationship with preterm delivery at the Alfredo Noboa Montenegro Hospital, August-November 2022" was developed with the objective of "Identifying the main risk factors in preeclampsia and its relationship with preterm delivery, in patients attending the Alfredo Noboa Montenegro Hospital" through a quantitative approach research of descriptive level of longitudinal design and the use of instruments such as the questionnaire and the data collection form. By means of a survey it was determined that the non-modifiable risk factors related to severe preeclampsia were: extreme age in 12.5% of the patients, housing conditions with 62.5% coming from rural areas, low schooling with 37.5% with only basic level, high blood pressure in family members or in previous pregnancies in 12.5% of the patients, obesity in 50% of the patients, chronic hypertension in 75% of the pregnancies and 12.5% of women with preeclampsia in previous pregnancies. With the information gathered, it is concluded that severe preeclampsia is associated with preterm delivery and that the prevalence of severe preeclampsia in pregnant patients attended at the Alfredo Noboa Montenegro Hospital in the period August-November 2022 was 5.12% and 1.64% of preterm deliveries due to severe preeclampsia for the total number of live births. This is associated with various risk factors; therefore, it was recommended that the first level of care be strengthened in order to achieve adequate recruitment and management of pregnant women for the control and prevention of risk factors during pregnancy. Key words: preterm delivery, preeclampsia, risk factors